Internal and external loads of young elite soccer players during defensive small-sided games - Rabano-Muñoz, A.; Suarez-Arrones, L.; Requena, B.; Asian-Clemente, J. A. (Journal of Human Kinetics, 2023)
The aim of this study was to evaluate the effects of different time periods on the internal and external loads of soccer players during small-sided games (SSGs). Seventeen young soccer players performed a SSG of 5 vs. 5 + 5 with 2 floaters, where two teams had possession of the ball, and one had to recover it. With established periods of 30 s (SSG30), 1 min (SSG1) or 2 min (SSG2), teams participated in a defensive role for these periods of time. Total distance covered, moderate speed running distance, high speed running distance, sprint running distance, accelerations, decelerations and Player Load were monitored using global positioning systems devices. The maximal heart rate and modified training impulse were monitored using heart rate monitors. The rating of perceived exertion (RPE) was also measured. Data showed a small increase between SSG30 and SSG1 in Player Load (ES = -0.35; p < 0.01), and a small increase in high speed running (ES = -0.41; p < 0.05) and sprinting (ES = -0.47; p < 0.01) between SSG30 and SSG2. Also, SSG1 showed a small increase in sprinting (ES = -0.57; p < 0.01) and accelerations (ES = -0.37; p < 0.05) with respect to SSG2. In addition, SSG2 showed a small increase in the RPE with respect to SSG30 (ES = 0.46; p < 0.05). The results indicate that shorter defensive periods in SSGs increased high speed running, while longer defensive periods promoted greater perceived exertion. Manipulation of the duration of defensive periods in SSGs is a variable that should be considered in soccer training.